Plant species abundance and phylogeny explain the structure of recruitment networks. Issue 1 (26th March 2019) - Alcántara, Julio M.; Garrido, José L.; Rey, Pedro J.
Summary: Established plants can affect the recruitment of young plants, filtering out some and allowing the recruitment of others, with profound effects on plant community dynamics. Recruitment networks (RNs) depict which species recruit under which others. We investigated whether species abundance and phylogenetic distance explain the structure of RNs across communities. We estimated the frequency of canopy–recruit interactions among woody plants in 10 forest assemblages to describe their RNs. For each RN, we determined the functional form (linear, power or exponential) best describing the relationship of interaction frequency with three predictors: canopy species abundance, recruit species abundance and phylogenetic distance. We fitted models with all combinations of predictor variables, from which we simulated RNs. The best functional form of each predictor was the same in most communities (linear for canopy species abundance, power for recruit species abundance and exponential for phylogenetic distance). The model including all predictor variables was consistently the best in explaining interaction frequency and showed the best performance in predicting RN structure. Our results suggest that mechanisms related to species abundance are necessary but insufficient to explain the assembly of RNs. Evolutionary processes affecting phylogenetic divergence are critical determinants of RN structure.